MODERASI PENDIDIKAN ISLAM DI INDONESIA - Asrori, Achmad; Sunarto, Sunarto; Istihana, Istihana (Universitas Islam Lamongan, 2024)
This research aims to determine the conception of moderation in Islamic education that can be applied in the educational environment. Mengan uses a systematic literature review to collect data using books and scientific journals. The results of this research regarding Moderation of Islamic education is an effort in education that brings Islamic values that can be accepted by all groups and is in accordance with needs without having to discriminate or dichotomy in its implementation, but prioritizing diversity in various aspects of Islamic education, both from planning, content and implementation.